2007
DOI: 10.1128/mcb.00315-07
|View full text |Cite
|
Sign up to set email alerts
|

PITX2 and β-Catenin Interactions Regulate Lef-1 Isoform Expression

Abstract: Lef-1 and PITX2 function in the Wnt signaling pathway by recruiting and interacting with ␤-catenin to activate target genes. Chromatin immunoprecipitation (ChIP) assays identified the Lef-1 promoter as a PITX2 downstream target. Transgenic mice expressing LacZ driven by the 2.5-kb LEF-1 promoter demonstrated expression in the tooth epithelium correlated with endogenous Lef-1 FL epithelial expression. PITX2 isoforms regulate the LEF-1 promoter, and ␤-catenin synergistically enhanced activation of the LEF-1 prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 43 publications
2
105
0
1
Order By: Relevance
“…Pitx2 binds to the 5Ј-TAATCC-3Ј DNA sequence to regulate gene expression. Chromatin immunoprecipitation assays have previously demonstrated that Pitx2 binds to the Lef-1 promoter and synergistically regulates Lef-1 isoform expression in concert with Lef-1 and ␤-catenin (25,32). In this report we have identified a new transcriptional mechanism, where the Dlx2 protein has a repressive effect on PITX2 activation of the Dlx2 promoter.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Pitx2 binds to the 5Ј-TAATCC-3Ј DNA sequence to regulate gene expression. Chromatin immunoprecipitation assays have previously demonstrated that Pitx2 binds to the Lef-1 promoter and synergistically regulates Lef-1 isoform expression in concert with Lef-1 and ␤-catenin (25,32). In this report we have identified a new transcriptional mechanism, where the Dlx2 protein has a repressive effect on PITX2 activation of the Dlx2 promoter.…”
Section: Discussionmentioning
confidence: 67%
“…Chromatin Immunoprecipitation (ChIP) Assay-The ChIP assays were performed as previously described using the ChIP assay kit (Upstate Biotechnology) with the following modifications (24,25). LS-8 cells were fed for 24 h, harvested, and plated in 60-mm dishes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, paired-like homeodomain transcription factor-2 (Pitx2) is known to upregulate the expression of Lef1, hence the decrease in Pitx2 expression (Table 1) appears to explain the decrease in Lef1 expression. 35 The differential expression of Lef/Tcf family members in 10T1/2 stem cells and committed A33 preadipocytes is likely to be important in determining their respective phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Pitx2 is the first transcriptional marker of tooth development and Pitx2 null mice have tooth development arrest at E12.5 (Liu et al, 2003;Lu et al, 1999). We have previously shown that Pitx2 regulates Lef-1 expression during odontogenesis (Amen et al, 2007;Vadlamudi et al, 2005). RNAsequencing data showed that Sox2 expression was upregulated in the mandibles of Pitx2 overexpression mice and downregulated in the mandibles of Pitx2 null mice (B.A.…”
Section: Sox2 Attenuates Pitx2 Transcriptional Activation Of Lef-1 Smentioning
confidence: 99%